Niejawne społeczności wirtualne jako źródło wiedzy przedsiębiorstwa - Pawełoszek-Korek, Ilona (Hidden Web Communities as Sources of Knowledge for an Enterprise, 2007)
This paper addresses the detection and analysis of hidden Web communities based on information available from Web, such as Web document content and hyperlinks. Web communities are interesting research domain and they can become a valuable resource of knowledge for business intelligence systems of an enterprise. Applications of aforementioned methods are another aspect emphasized in this paper. Before presenting various approaches to detect and analyze hidden web communities, some definitions of hidden web communities are provided according to different authors.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (10); 2007; nr 1150, s. 246-253